MONITORING OF CORRUPTION AND ANTICORRUPTION POLICY MEASURES IN THE REPUBLIC OF TATARSTAN: ISSUE OF THEORY AND PRACTICE - A. Yu. Pankratov (Russian Journal of Economics and Law)
The article views the issues of regional anticorruption monitoring in the Republic of Tatarstan. The corruption in the Republic is characterized, anticorruption measures are evaluated.